Pengaruh Debt Covenant Dan Tunneling Incentive Terhadap Transfer Pricing - Daffa Aulia Albani; Juniati Gunawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Abstract: This study aims to examine and analyze the relationship between Debt Covenants and Tunneling Incentives on transfer pricing, with company size as the control variable for companies listed on the Indonesia Stock Exchange during 2019-2021. The population used in this study are companies from the manufacturing industry sector which are listed on the Indonesia Stock Exchange which also publish Financial Statements for 2019-2021. The samples in this study were 41 companies and the total number of observations was 123. The data collection method was downloaded from the IDX website. The analytical method used is multiple linear regression analysis. The results of testing the hypothesis in this study indicate that the Tunneling Incentive variable has a positive and significant effect on transfer pricing with firm size as the control variable, while the Debt Covenant variable has no positive and significant effect on transfer pricing with firm size as the control variable. Keywords: Transfer Pricing, Debt Covenant, Tunneling Incentive, Company size.